Challenges in Health Care, Diet and Nutrition in Polycystic Ovarian Syndrome. (14th June 2022) - Wilke, Michaelann; Ghosh, Mahua; Vine, Donna
Abstract: Objectives: Polycystic Ovarian Syndrome (PCOS), the most common endocrine-metabolic disorder in women, is associated with a higher incidence of obesity, metabolic syndrome, Type 2 Diabetes and Cardiovascular Disease. The recommended first line targets are diet, lifestyle and behaviour in managing body weight and adverse health outcomes. The objective of this study was to assess the health status, health care experience and supports related to nutrition and lifestyle in people with PCOS. Methods: Respondents completed a retrospective survey online between Jan 2021-Jan 2022 and included Alberta (Canada) residents who self-reported a diagnosis of PCOS (n = 145). The survey was based on previous validated health and quality of life surveys in PCOS, expanded, and re-validated in PCOS patients and health care providers in Alberta. Themes of questions on diagnosis, referral to health care providers, health concerns, diet and nutrition were analyzed. Results: The majority of respondents were aged 26 to 45 yrs of age (84%), self-reported overweight or obesity (96%) and were residents of Alberta for > 10 years (85%). In 34% of respondents a diagnosis of PCOS took > 2 years, and 60% reported visiting more than one healthcare provider before a final PCOS diagnosis. Many respondents (75%) were not informed of the health risks associated with PCOS. Following a PCOS diagnosis, 23% were diagnosed with high blood cholesterol and 25% with prediabetes or diabetes. Most respondents (> 80%) were not referred to a Registered Dietitian or other health care provider to manage PCOS symptoms and cardiometabolic risk factors. A lack of nutrition knowledge was reported as a major barrier to losing weight (38%), however the most common barriers cited were stress (75%) and negative feelings (60%). A priority recommendation by respondents to improve their health care included better education in diet-nutrition. Conclusions: This data provides evidence for the need to develop preventative health care strategies to improve overall health, referral and access to diet-nutrition counseling in this high-risk PCOS population in Alberta, Canada. Funding Sources: Women and Children's Health Research Institute.